2009
DOI: 10.1358/dot.2009.45.6.1378934
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the literature: Role of trabectedin as a new chemotherapy option in advanced pretreated soft tissue sarcoma

Abstract: This bibliographic review evaluated phase II clinical trials aimed at the identification of antitumor activity of single agents in soft tissue sarcoma (STS) after failure of standard- of-care therapy including anthracyclines and ifosfamide. A total of 63 articles (on anthracyclines, ifosfamide, trabectedin and 27 investigational agents) were included (data from 1979 to 2008).Trabectedin is the most extensively studied agent in patients with STS after failure of anthracyclines and ifosfamide (457 patients), fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…Our results show that trabectedin is an active treatment with an overall ORR of 10.0% (younger: 10.1% vs older: 9.6% patients). This ORR is comparable to that reported with low-dose ifosfamide (14%) and doxorubicin (13%) in pre-treated STS patients (Le Cesne et al , 2009). This benefit in both younger and older patient population was further confirmed by PFS rates at 3 months (45.1% vs 55.1%) and 6 months (29.5% vs 36.4%).…”
Section: Discussionsupporting
confidence: 82%
“…Our results show that trabectedin is an active treatment with an overall ORR of 10.0% (younger: 10.1% vs older: 9.6% patients). This ORR is comparable to that reported with low-dose ifosfamide (14%) and doxorubicin (13%) in pre-treated STS patients (Le Cesne et al , 2009). This benefit in both younger and older patient population was further confirmed by PFS rates at 3 months (45.1% vs 55.1%) and 6 months (29.5% vs 36.4%).…”
Section: Discussionsupporting
confidence: 82%
“…Although, the predominant toxicities at the RD of 1.3 mg/m 2 in those studies (fatigue, transient neutropenia and transient transaminase) were similar to these observed in our study, no cumulative hematological toxicity have been observed; neutropenia and thrombocytopenia were always transient with rapid recovery (5-7 days) and rarely associated with febrile neutropenia and/or neutropenic infection [7,[28][29][30]. Therefore, the cumulative hematological toxicity and the higher incidence of severe neutropenia (59.0% vs. ∼25.0% with trabectedin as single agent) and thrombocytopenia (47.7% vs. 7-19% with trabectedin as single agent) found in the current phase I trial is more due to carboplatin than to trabectedin itself [7,31]. In recent phase I study the combination of trabectedin and cisplatin have achieved lower RDs, ranging between 0.5 and 0.6 mg/m 2 [14].…”
Section: Discussionmentioning
confidence: 81%
“…Other studies that investigated the efficacy and safety of drugs not approved for mSTS were not considered. Typically, mSTS studies were also hindered by poor follow-up (compare Le Cesne et al [12]). Since the period of interest was the duration PD → death, poor follow-up could have biased the results.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that TRA arrests STS growth in ∼40%–60% of tumours [811] and produces significant clinical benefit in patients with STS progression after A/I [9]. At doses used clinically, TRA is well tolerated [12]. The safety and efficacy of TRA shown in clinical trials have been confirmed in compassionate use [8].…”
Section: Introductionmentioning
confidence: 99%